Réponses

2013-05-12T12:29:07+02:00

C'est tout simple, sachant que :

A = 4x² - 3x - 5

 

a) Si x vaut 1 :

A = 4 x 1² - 3 x 1 - 5

   = 4 - 3 - 5

   = 1 - 5

   = -4

 

b) Si x vaut -1 :

A = 4 x (-1)² - 3 x (-1) - 5

   = 4 - (-3) - 5

   = 4 + 3 - 5

   = 7 - 5

   = 2

 

c) Si x vaut 3 :

A = 4 x 3² - 3 x 3 - 5

   = 36 - 9 - 5

   = 27 - 5

   = 22

 

d) Si x vaut -2 :

A = 4 x (-2)² - 3 x (-2) - 5

   = 4 x 4 - (-6) - 5

   = 16 + 6 - 5

   = 22 - 5

   = 17

 

Voila pour l'exercice 71.

2013-05-12T12:32:53+02:00

Ex 71 : A) 4 x 1x1 -3x1-5

                 -4

 

b) 4x(-1)x(-1)-3x(-1)-5

2

c) 4x3x3-3x3-5

22

d) 4x(-2)x(-2)-3x(-2)-5

17